Development of canned meat production technique and its quality assessment: Development of canned meat production technique - Roy, B K; Khanam, J S; Tule, S A; Sultana, N (Bangladesh Journal of Animal Science, 2025)
This study was undertaken to produce canned meat following an effective and cost-effective technique for having safe and hygienic ready product to cook along with the determination of its preservation quality. Raw boneless meat (beef, chevon and broiler chicken) collected from local market were subjected to three treatments (addition of two different preservatives and no preservative) with three replications of each. Beef, chevon and chicken were considered meat type and Na-Nitrite (150g/kg) and Nacl (5g/kg) were the used preservatives. Fresh meat quality was compared in ANOVA of CRD and canned meat were in 3*3 factorial design using GLM of SPSS 17.0. Meat was canned using pressure canner at 240˚ F and 10 lb pressure for 90 minutes. No change in color, texture and flavor was found in canned meat up to 30 days of storage period. Both pH and protein level were influenced by canning where increasing trend was observed compared to fresh meat. In case of pH, chicken meat treated with Na-Nitrite had higher pH (p<.001) irrespective of meat and preservative type. In result, a scientific meat canning technique was developed through this study and considering the physico-chemical aspects Na-Nitrite could be a suitable preservative for meat canning. Bangladesh Journal of Animal Science 54(1): 12-19, 2025